Ichnological and Sedimentological Characteristics of Submarine Fan-Delta Deposits in a Half-Graben, Lower Cretaceous Palnatokes Bjerg Formation, NE Greenland. Issue 1 (2nd January 2019) - Hovikoski, Jussi; Uchman, Alfred; Alsen, Peter; Ineson, Jon
ABSTRACT: Fault-scarp related fan deltas developed in tilted half grabens in NE Greenland during late Jurassic—early Cretaceous rifting. This study documents ichnological and sedimentological characteristics of the Lower Cretaceous interval of a submarine fan-delta succession (Palnatokes Bjerg Formation, Wollaston Forland), which represents a time of waning rift activity and transgression. For this purpose, two variably exposed ca. 150 m-thick sections were studied ∼10 km from the coeval fault scarp, near the axis of the most proximal fault block. Moreover, an additional ∼20 m thick coeval succession was studied in the next fault block ∼20 km from the coastline defining fault. The results indicate deposition on the basin floor, in the distal fan and in a mid-fan channel-overbank/splay complex of a subaqueous fan delta. The deposits are characterized mainly by various facies of high and low density turbidity currents, hybrid event beds, and transitional flow facies that grade upward into sediment starved basinal mudstones. The ichnological pattern recorded in these strata is strongly mixed, frequently containing elements of the impoverished Skolithos, Cruziana, Zoophycos ichnofacies, and more rarely of the Nereites ichnofacies. Characteristic features also include suites dominated by infaunal locomotion and feeding trails (including the " Curvolithus suite") and the common occurrence of crustacean burrows. The results are indicative of a depositional system resembling a fjord-side delta that differs sedimentologically and ichnologically from many other gravity-flow systems of similar grain-size caliber. The ichnological pattern recorded in these strata is potentially a characteristic feature of the subaqueous fan-deltas in comparable settings, reflecting the distinct basin physiography with an abrupt change in bathymetry, a narrow basin geometry, and environmental stress resulting from unstable physical conditions. The counter slope of the rotated fault block may explain the common signs of flow concentration and abrupt fan termination.